If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 3x + 5y(y + 5) = -33 Reorder the terms: 3x + 5y(5 + y) = -33 3x + (5 * 5y + y * 5y) = -33 3x + (25y + 5y2) = -33 Solving 3x + 25y + 5y2 = -33 Solving for variable 'x'. Move all terms containing x to the left, all other terms to the right. Add '-25y' to each side of the equation. 3x + 25y + -25y + 5y2 = -33 + -25y Combine like terms: 25y + -25y = 0 3x + 0 + 5y2 = -33 + -25y 3x + 5y2 = -33 + -25y Add '-5y2' to each side of the equation. 3x + 5y2 + -5y2 = -33 + -25y + -5y2 Combine like terms: 5y2 + -5y2 = 0 3x + 0 = -33 + -25y + -5y2 3x = -33 + -25y + -5y2 Divide each side by '3'. x = -11 + -8.333333333y + -1.666666667y2 Simplifying x = -11 + -8.333333333y + -1.666666667y2
| (4x+15)=45+12x | | 24*5v/8 | | y/-6=-10 | | -5=14x | | x^3-x^2=36 | | 9p=54iswhat | | 5(x/4)=7(x-2) | | 4+x+2-2=5 | | 4(2x-5)=3(x+10)-15 | | x^2+8x-731=0 | | 2n/-6 | | 30x/5x= | | 2b+6=3b+6 | | 3=18/x-18 | | x^3/x= | | 3[0.2x+(-2)]= | | 13x-2x-3x=66 | | 6x(x-1)+13=7 | | 1/14(0-8)-9 | | g(b+6)=3x-1 | | 3b^3+9b^2= | | 8(w-6)-(7-4w)=11w | | 8x=20/75 | | 3x/5=-4/9 | | (X^2+1)(x^4-2x^3-5x^2-6x)=0 | | -6w+12=42 | | -9=1-5w | | 28x^2-61+21=0 | | -29=4w-9 | | -11-3y=7 | | 4(2y+1)=34 | | 4x+-3(x+5)=10 |